A new approach to drug development – the success story of Gertrude Elion, a Nobel laureate - M. V. Grigorieva; T. M. Petrenko; V. M. Danilova; S. V. Komisarenko (The Ukrainian Biochemical Journal)
Gertrude Elion is one of the most prominent figures in the world of science of the 20th century. In 1988, her achievements in the field of pharmacology were recognized at the highest level – she won the Nobel Prize in Physiology or Medicine. Together with George Hitchings and Sir James Black, she received this award “for their discoveries of important principles for drug treatment”, the principles that led to the development of new drugs. Her methods featured an unconventional approach: she sought to create drugs that selectively affected disease-causing cells, thus minimizing side effects. Her research paved the way for what we call today the targeted therapy concept. Elion’s whole life is a success story of a scientist who achieved brilliant results thanks to her tireless work and dedication to science. This article reviews the life and discoveries of Gertrude Elion and explains why her work is still relevant for present-day medicine.